TANGGUNG JAWAB KORPORASI DALAM TINDAK PIDANA DI BIDANG PERPAJAKAN (ANALISIS TERHADAP PUTUSAN MAHKAMAH AGUNG NO. 2239 K/PID.SUS/2012) - Herbert Rumanang; Bismar Nasution; Mahmul Siregar; Mahmud Mulyadi (USU LAW JOURNAL, 2016)
ABSTRACTIn general, the legal subject which is commonly known in penal law is person. However, as of the development of law, another legal subject starts to take place, which is corporation. That means corporation is treated as if it is an ordinary person that has criminal liability. The acknowledgement of corporation as a penal law subject is recognized in various particular legislations in Indonesia, including taxation law. This concept is known in term as corporate crime and corporate criminal liability. One example of how this concept is applied in Indonesian law can be seen in the Supreme Court verdict no. 2239 K/Pid.Sus/2012 which convicted Asian Agri as a corporation for committing tax crime. While the Indonesian penal law system acknowledges the existence of corporation as a legal subject, such condition causes legal implication which is not simple. This is due to the nature and characteristic of corporation which are basically different from the nature and characteristic that we can find in a person. The consequence is that the theories of criminalization which are the theoretical basis to convict should be distinguished between corporation and person because they are also based on different paradigms. In the Supreme Court verdict no.2239 K/Pid.Sus/2012 Asian Agri is sentenced to pay a fine of 2.52 trillion rupiahs as a form of corporate criminal liability. Despite so, the verdict itself is not without weaknesses in its application of law. Those weaknesses are as follow: Asian Agri is not a party in that case, Suwir Laut as the accused is not a director of Asian Agri, the fine sentence as a trial condition, and the establishment of the fine amount by the Supreme Court.Key words: corporate crime, corporate criminal liability